Iron Dyshomeostasis Induces Binding of APP to BACE1 for Amyloid Pathology, and Impairs APP/Fpn1 Complex in Microglia: Implication in Pathogenesis of Cerebral Microbleeds. Issue 8 (August 2019) - Gong, Li; Tian, Xiangzhu; Zhou, Jing; Dong, Qiong; Tan, Yan; Lu, You; Wu, Jiayan; Zhao, Yanxin; Liu, Xueyuan
As a putative marker of cerebral small vessel disease, cerebral microbleeds (CMBs) have been associated with vascular cognitive impairment. Both iron accumulation and amyloid protein precursor (APP) dysregulation are recognized as pathological hallmarks underlying the progression of CMBs, but their cross-talk is not yet understood. In this study, we found a profound increase of amyloid formation with increasing FeCl3 treatment, and a distinct change in APP metabolism and expression of iron homeostasis proteins (ferritin, Fpn1, iron regulatory protein) was observed at the 300 uM concentration of FeCl3 . Further results revealed that extracellular iron accumulation might potentially induce binding of APP to BACE1 for amyloid formation and decrease the capability of APP/Fpn1 in mediating iron export. Our findings in this study, reflecting a probable relationship between iron dyshomeostasis and amyloid pathology, may help shed light on the underlying pathogenesis of CMBs in vascular cognitive impairment.